2014
DOI: 10.1603/me12223
|View full text |Cite
|
Sign up to set email alerts
|

An Insight Into the Microbiome of theAmblyomma maculatum(Acari: Ixodidae)

Abstract: The aim of this study was to survey the bacterial diversity of Amblyomma maculatum Koch, 1844, and characterize its infection with Rickettsia parkeri. Pyrosequencing of the bacterial 16S rRNA was used to determine the total bacterial population in A. maculatum. Pyrosequencing analysis identified Rickettsia in A. maculatum midguts, salivary glands, and saliva, which indicates successful trafficking in the arthropod vector. The identity of Rickettsia spp. was determined based on sequencing the rickettsial outer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
133
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(142 citation statements)
references
References 69 publications
9
133
0
Order By: Relevance
“…Moreover, humans and animals bitten by these ticks were seropositive to the endosymbiont bacterial antigens [38, 39]. Further, Budachtri et al [40] showed that Amblyomma maculatum were predominantly infected with Francisella, Wolbachia and rickettsial species and sequences corresponding to rickettsial outer membrane protein-encoding genes ( ompA and ompB ) were also observed in salivary glands suggesting that these endosymbionts had the potential for transmission to the vertebrate host. While most tick-borne endosymbionts were thought to be innocuous passengers [22, 41], these observations question that presumption.…”
Section: Intracellular Endosymbionts Of Ticksmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, humans and animals bitten by these ticks were seropositive to the endosymbiont bacterial antigens [38, 39]. Further, Budachtri et al [40] showed that Amblyomma maculatum were predominantly infected with Francisella, Wolbachia and rickettsial species and sequences corresponding to rickettsial outer membrane protein-encoding genes ( ompA and ompB ) were also observed in salivary glands suggesting that these endosymbionts had the potential for transmission to the vertebrate host. While most tick-borne endosymbionts were thought to be innocuous passengers [22, 41], these observations question that presumption.…”
Section: Intracellular Endosymbionts Of Ticksmentioning
confidence: 99%
“…Different studies have used different hypervariable regions of the 16S rDNA [56] (V1-V3, V4, V5, or V6, regions) and examined different tick stages from diverse geographic locations in the world (Table 1). Further, while most studies have utilized whole ticks, only a handful has utilized specific tissues dissected from the ticks [40, 57-59]. The limitation of using whole ticks is that it does not allow one to define the tissue-specific microbiome [60] and this understanding might be pertinent to derive functional inferences in the context of the biology of the tick and its interactions with tick-borne pathogens.…”
Section: Beyond the Intracellular Endosymbiontsmentioning
confidence: 99%
See 1 more Smart Citation
“…While there have been many studies of tick microbiomes (11)(12)(13)(14)(15)(16)(17), relatively little is known about the microbiota of Ixodes ticks. Efforts to identify microbial commensals and symbionts have been made using culture-based methods (18), cloning, and sequencing of gel-purified PCR products (4).…”
mentioning
confidence: 99%
“…This study revealed the presence of bacteria of 121 genera, including Borrelia, Coxiella, Wolbachia and Legionella. Among others, microbiomes of Ixodes ricinus [25], Amblyomma testudinarium, Amblyomma variegatum, Haemaphysalis formosensis, Haemaphysalis longicornis, Ixodes ovatus, Ixodes persulcatus [26], Amblyomma americanum [27], and Amblyomma maculatum [28] were analyzed. 454-and Illumina-based metagenomic approaches were used along with pyrosequencing of bacteriaenriched whole genome or prokaryotic 16S rRNA.…”
Section: Microbiome Studiesmentioning
confidence: 99%